Assessment of scatterometer data for environmental studies in the Thar Desert - Stephen, Haroon; Schumann, Robert L. G.; Honda, Kiyoshi; Kaew Nualchawee; Government of Japan (Bangkok : Asian Institute of Technology, 1997)
Since summer 1991 the scatterometer aboard European Remote Sensing Satellites ERS-1 and ERS-2 have provided global radar backscatter measurements of the Earth's surface. Over the oceans these data are used operationally for wind field retrieval. Simultaneously possible applications of these low resolution data over land surfaces were studied by numerous investigators. Due to the global coverage, the continuity of the data and the wide range of incidence angle these data have been found to provide valuable information despite the coarse resolution. In this research normalized radar cross section (NRCS) measurement obtained over Thar desert in Pakistan between August 1991 and December 1996 are analyzed. Spatial variations in the radar cross section are compared with rainfall and vegetation parameters. Inter-annual as well as intra-annual variations in radar backscatter are investigated and are found to be effected by rainfall. Zonal characterization of area is made on the basis of radar backscatter behavior. It is found that vegetation parameters of the land are reflected in the incidence angle diversity of the ERS scatterometer. The NRCS and Advanced Very High Resolution Radiometer (A VHRR) data for 1994 are compared and radar backscatter is also found to be correlated with Normalized Difference Vegetation Index (NDVI). It is demonstrated that valuable information can be delineated from the ERS scatterometer data over arid regions in order to provide data for environmental and especially climatic monitoring.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1997
Keywords: Remote sensing -- Thar Desert; Environmental sciences -- Thar Desert